Structural and ultrastructural characterization of buffalo fetus (Bubalus bubalis) ovarian germinative cells - Carvalho, F. C. A. [UNESP]; Oba, Eunice [UNESP]; Mota, A. V. [UNESP]; Leal, L. S. [UNESP] (Pagepress Publ, 2007)
The objective of the present study was to characterize ovogones, primary oocytes and preantral follicles of buffalo fetus in different ages of gestation. For this, 29 fetuses were collected from a slaughterhouse (Frigol, Brazil) and crown-rump lengths were measured to estimate the fetal age (0-3, 4-6, 7-10 months of gestation). The ovaries were removed and ovarian tissue was processed for classic histology and transmission eletron microscopy examination. The structural evaluation demonstrated that in the first period of the gestation (0-3 months) the buffalo fetus showed ovogones (in mitotic division) and in some cases, the primary oocytes surrounded by somatic cells. In the second period (4-6 months), it was verified that the preantral follicles were completely formed. In the last period (70 month to the end of gestation) the ovaries contained a large amount of preantral follicles, and in some fetuses, antral follicles were observed. The ultrastructural analysis of the ovogones, primary oocytes and preantral follicles showed that these cells have few organelles and the quantity of mitochondria, endoplasmatic reticulum and apparatus Golgi complex is increased as the germinative cells passing from one stage to another.
Keywords: Buffalo; Fetus; Ovarian follicles; Histology